(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Active travel (walking, cycling, wheeling) and public transport provide considerable benefits for physical activity, public health, and environmental sustainability. As the population ages, cities such as Glasgow face increasing challenges to ensure that sustainable transport systems are both accessible and inclusive for older adults, who frequently encounter a range of barriers limiting their participation. Given the heterogeneity within this demographic, certain sub-groups may be at risk of exclusion, potentially exacerbating existing inequalities. To address these issues, a comprehensive understanding of older adults’ experiences with active and sustainable travel is essential. This project will undertake a systematic review to identify the enablers and barriers influencing older adults’ use of sustainable transport and will explore the lived experiences of older adults engaging with sustainable travel in Glasgow (United Kingdom). Methods: A systematic review will be conducted using SCOPUS, TRID, Web of Science, AgeLine, and EMBASE. Studies will be included if they address: (1) active and/or public transport, (2) older adults (aged 60+), and (3) enablers or barriers to use. Only studies from developed countries published in the last 20 years will be considered. Both qualitative and quantitative research will be included. Data will be managed in Covidence, with qualitative data analysed thematically using NVivo and quantitative findings synthesised narratively. The review will inform a qualitative study with approximately 20 older adults in Glasgow, using photo elicitation interviews, demographic surveys, and assessments to explore the diversity of their needs. Results: Database searches are underway, with interviews to be conducted in Summer 2025. Findings from the review and interviews will inform co-design workshops with older adults, policymakers, practitioners, and researchers. These workshops will generate practical, community-led recommendations to enhance sustainable transport access in Glasgow. Conclusion: Creating inclusive sustainable transport systems that reflect the diverse needs of older adults is essential for promoting physical activity, improving health, reducing inequalities, and responding to the climate emergency. This project will support practitioners and policymakers in designing targeted, evidence-based interventions that embed older adults’ needs in future transport planning. Support/Funding Source: Carnegie Trust for the Universities of Scotland.